2019
DOI: 10.1016/j.drugalcdep.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Substance abuse and white matter: Findings, limitations, and future of diffusion tensor imaging research

Abstract: Individuals who abuse substances often differ from nonusers in their brain structure. Substance abuse and addiction is often associated with atrophy and pathology of grey matter, but much less is known about the role of white matter, which constitutes over half of human brain volume. Diffusion tensor imaging (DTI), a method for non-invasively estimating white matter, is increasingly being used to study addiction and substance abuse. Here we review recent DTI studies of major substances of abuse (alcohol, opiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 115 publications
5
75
1
Order By: Relevance
“…Substance abuse is a classic model of reward seeking gone awry. We recently reviewed the diffusion imaging literature on substance abuse (Hampton, Hanik, & Olson, 2019) and found that the literature was highly inconsistent, even when restricted to a particular substance like cocaine. The fornix was mentioned as being affected in only a single study of adolescents with alcohol use disorder (Cardenas et al, 2013).…”
Section: The Fornix In Aberrant Reward-seeking: Eating Disorders and mentioning
confidence: 99%
“…Substance abuse is a classic model of reward seeking gone awry. We recently reviewed the diffusion imaging literature on substance abuse (Hampton, Hanik, & Olson, 2019) and found that the literature was highly inconsistent, even when restricted to a particular substance like cocaine. The fornix was mentioned as being affected in only a single study of adolescents with alcohol use disorder (Cardenas et al, 2013).…”
Section: The Fornix In Aberrant Reward-seeking: Eating Disorders and mentioning
confidence: 99%
“…Although most neuroimaging studies have examined the chronic cocaine use (CU) effects on specific gray matter brain regions, several recent investigations have focused on revealing the white matter (WM) signature of CUD 7 . Diffusion-weighted imaging (DWI) is a magnetic resonance sequence that captures water diffusion properties in the brain and has been frequently used in studies that determined the fibers and tracts that are progressively deteriorated because of repeated cocaine consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Large studies report some differences in prefrontal gray matter, with deficits associated with addicted populations (Xiao et al, 2015; Yuan et al, 2010). They also suggest deficits in the white matter tracts that provide the pathway whereby the prefrontal cortex exerts influence over subcortical signaling (Hampton, Hanik, & Olson, 2019). Other work suggests relevant neurotransmitter deficits in addicted populations, including a deficiency in dopamine projecting to the prefrontal cortex, which supports executive function (Koob & Volkow, 2010; Martinez et al, 2012; Volkow, Fowler, Wang, Baler, & Telang, 2009).…”
Section: Scientific Explanations and Antecedents To Psychological Statesmentioning
confidence: 99%